East or west: to which subspecies does the type specimen of the Galah, Eolophus roseicapilla (Vieillot, 1817) (Aves: Cacatuidae), belong? - Schodde, Richard; Black, Andrew B.; Fornasiero, F. Jean (Zootaxa, 2016)
The Galah (Eolophus roseicapilla) is a pink-and-grey cockatoo, widespread in and endemic to Australia, and now familiar as a cage bird world-wide. It has three currently recognised subspecies: roseicapilla Vieillot, 1817 in the Australian west, kuhli Mathews, 1912 in the far north, and albiceps Schodde, 1989 in the east (Schodde 1997; Higgins 1999; Dickinson & Remsen 2013; del Hoyo & Collar 2014; Engelhard et al. 2015). The northern subspecies, kuhli, is not involved in the issue of type identity of roseicapilla, and so is not considered further here. First to distinguish east and west subspecies was G.M. Mathews (1912). Without explanation then or later, Mathews arbitrarily applied the senior specific name, Cacatua roseicapilla Vieillot, 1817 and its two objective synonyms based on the same type—eos Kuhl, 1820 and rosea Vieillot, 1822—to the eastern subspecies, and introduced the new name assimilis for the then supposedly undescribed western form. Mathews’ lead was followed unquestioningly until the late 1980s when Schodde (1989) and Rowley (1990: 3) concluded that the type of Vieillot’s roseicapilla was of the western subspecies, collected by the Baudin expedition in the region of Shark Bay on the mid-western Australian coast. Rowley (l.c.), but not Schodde (l.c.) contrary to Rowley’s reference, went further to claim that it had been taken by François Péron in 1803, presumably on the brief return visit of Baudin in Le Géographe to Shark Bay en route to France. This left the eastern subspecies un-named, which Schodde (l.c.) accordingly described as albiceps.